Effectiveness of Problem Based Learning Model with Worksheet Assisted on Students' Critical Thinking Ability - Satutik Rahayu; Ni Nyoman Sri Putu Verawati; Andi Fatimatul Islamiah (Lensa: Jurnal Kependidikan Fisika, 2019)
This research aims to know the effectiveness of the learning problem based learning model assisted worksheet for the critical thinking ability of physics students of grade X SMAN 1 Lingsar. This was an experiments research that using design research Posttest-Only Control group Design. The population in this research were the whole grade X SMA Negeri 1 Lingsar in academics year 2016/2017. Sampling taken with using cluster random sampling technique with the students of class X MIA.A as experiment class and X MIA.D as control class. Research hypothesis was analysis with the t-test for one party (the party right). Based on the hypothesis test results obtained tcount> ttable at significance level of 5%, then it can be inferred that the model of learning problem based learning assisted work sheet effective for critical thinking ability of physics students SMAN 1 Lingsar.